Preparation approach effect on polyurethane/montmorillonite nanocomposites characteristics. (August 2015) - David, Geta; Drobota, Mioara; Simionescu, Bogdan C.
Segmented polyurethane/montmorillonite (MMT) nanocomposites have been obtained by solvent casting or in situ polymerization approaches using poly(tetramethyleneglycol), α, ω-dihydroxylated poly(2-alkyl-2-oxazoline), 4, 4′-methylenebis-(phenyl isocyanate) and MMT. The influence of the preparation method on the characteristics of the resulted materials was studied by means of spectral and thermal analysis, X-ray diffraction, scanning electronic microscopy, and dynamic-mechanical analysis.